High‐power impedance tuner utilising substrate‐integrated evanescent‐mode cavity technology and external linear actuators. Issue 12 (8th July 2019) - Semnani, Abbas; Shaffer, Garrett S.; Sinanis, Michael D.; Peroulis, Dimitrios
Abstract : A 100 W electronically controlled impedance tuner is introduced and experimentally investigated here. The proposed tuner is composed of two individually controlled coupled evanescent‐mode (EVA) cavity resonators implemented on a printed circuit board (PCB) using substrate‐integrated waveguide (SIW) technology. The contactless tuning mechanism relies on two high‐resolution external linear actuators controlling the gap size of each resonator with submicron accuracy. A 3.3 GHz prototype tuner successfully handled up to 100 W of input power with ∼90% Smith chart coverage at the centre frequency and about 52% bandwidth demonstrating at least 50% coverage. Exhibiting low loss of 0.56 dB and very high stability as well, the proposed impedance tuner is a viable solution for high‐power applications where electronic precise tuning is desired.